EFEKTIVITAS PENGGUNAAN APLIKASI E-TILANG BAGI KEPOLISIAN DALAM PROSES TILANG DI KOTA PEKANBARU - Rakha Ariyuna; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The E-Tilang program is a form of the National Police's seriousness in carrying out instructions from President Jokowi. The Police Headquarters Traffic Police, Inspector General Pol Agung Budi Maryoto, said that this program also aims to make the police more professional and even cut the bureaucratic chain. The application of this online-based system can prevent and reduce the practice of extortion (extortion) and make it easier for people to make ticket payment transactions. The purpose of this research to find out how effective the use of the E-Tilang application is for the police in the ticketing process in Pekanbaru City.The research method used in this research is quantitative. The population in this study was the Traffic Unit (Satlantas) Pekanbaru Police, amounting to 121 people. The sampling technique in this study is total sampling, which means that the number of samples is the same as the population, in other words all the total population in this study are defined as samples. The research data were collected by means of a questionnaire and documentation. The data measurement technique in this study uses a Likert scale. While the data analysis technique in this research is descriptive analysis.The results showed that the E-Tilang program was very beneficial for the Police and the people of Pekanbaru City. The E-Tilang program is considered to have a significant contribution to the work program of the Police in Pekanbaru City. With the E-Tilang program, the Police find it easier to compile data and carry out their duties as a civilian general institution that maintains order, security and law enforcement in all areas in Pekanbaru City. Of the five indicators that the author uses in this study, the average value is 3.46. This value is in the effective category with a score range of 3.41 - 4.20.